Educação em direitos humanos: diálogos e reflexões em uma escola pública da cidade de João Lisboa – MA - VIEIRA, Jaira Ruama Oliveira de Sousa (2022)
The present dissertation has as its object the Education in Human Rights and its possibilities of effectiveness in a public school of the municipal education network, from what is described in the Pedagogical Political Project and from the perspective of the education professionals who work there, showing how the human rights are presented in the guiding document of their educational practices and in the speeches and perceptions of the research subjects. The study was developed in a municipal institution of elementary education in the city of João Lisboa – MA, specifically during the shift in which elementary school work. The perspectives of each of the subjects involved in the provision and promotion of education at this stage of teaching were considered, in view of the human rights theme, its theoretical conceptualization and practical application for the effectiveness of the school as a protective and training space, in which the categories of sociopolitical awareness and the understanding of Human Rights Education as an essential formative element for a critical and liberating education overlap. The research was developed from a qualitative approach, of an exploratory and descriptive nature, which unfolded in field research and bibliographic survey, and its epistemological basis is based on a critical theory of reality, aligned with historical-dialectical materialism. The analysis of education, as a right and public policy, of human rights and sociopolitical awareness is made from the understanding of critical interculturality. Data were generated using systematic observation and conversation circles as instruments, and analyzed from a discursive perspective, due to the importance that the social context has on the senses and perceptions that subjects bring in their discourses. As a result, it was possible to identify that, in the researched school, the place of Human Rights is minimal and there is no discussion of issues related to these rights. Although the subjects recognize its importance, the implementation of the Human Rights Education encounters structural obstacles, from the education system that does not encourage them due to the lack of training in the area, whether initial or continuing; human obstacles, because, with the lack of training and pedagogical support, education professionals end up performing only common and restrictively content educational tasks, without a more significant and transforming practice; and obstacles in management, as there is a distance between what is described in the school's Pedagogical Political Project and what was observed in everyday life and described by the professionals who participated in the research, resulting in a school practice that does not expand the spaces for discussion, participation and transformation, and turning the school routine, which should be alive and dynamic, into something objectified and mechanical. It was also possible to identify that the theme of Human Rights is not recognized when implemented, even within the school, emphasizing that knowledge about the theme is incipient and insufficient for an effective implementation. Finally, it is concluded that human rights have a limited place in the daily life of the researched school and that there is a need to expand these spaces for the construction of a transformative educational practice.